Huanglongbing modifies quality components and flavonoid content of 'Valencia' oranges. (20th January 2015) - Massenti, Roberto; Lo Bianco, Riccardo; Sandhu, Amandeep K; Gu, Liwei; Sims, Charles
Abstract: BACKGROUND: In order to evaluate the effect of citrus greening disease, or Huanglongbing (HLB), on quality components and flavonoid contents of 'Valencia' oranges, fruit from non‐infected trees (control), from infected trees but symptom‐less (asymptomatic) and from infected trees and showing clear HLB symptoms (symptomatic) were harvested in March and in May, 2013. Fruit peel, pulp and juice were separated, the main quality components were determined, and hesperidin, nobiletin, tangeretin, narirutin and didymin were quantified using liquid chromatography. RESULTS: Peel colour, total soluble solids and citric acid were similar in control and asymptomatic fruits. Symptomatic fruits were smaller, yielded less juice, had higher acidity and lower sugar and peel colour than control fruits. In the peel, hesperidin, nobiletin, tangeretin, narirutin and didymin were higher in symptomatic than in asymptomatic and control fruits. Peel flavonoids decreased with fruit maturation. Also, in pulp and juice, flavonoid content was higher in symptomatic than in asymptomatic and control fruits. CONCLUSIONS: These results show that asymptomatic fruits are similar to control fruits more than to symptomatic fruits, suggesting that secondary metabolism and physical properties of fruits are only affected at a later and more advanced stage of HLB infection. Despite the significant loss of quality, fruit with clear HLB symptoms accumulate high quantities of flavonoids in peel and pulp. © 2014 Society of Chemical Industry